Penegakan Hukum Terhadap Kejahatan Pencurian Data Pribadi di Media Sosial (Facebook) - Arey, Muhammad Syaf Nurdin; Hehanussa, Deassy Jacomina Anthoneta; Salmon, Harly Cilford Jonas (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The rapid development of information technology has triggered an increase in digital activities, including the collection and storage of personal data. On the other hand, the phenomenon of theft of personal data and personal identity has become rampant and has caused increasingly significant losses, both materially and immaterially. This study aims to examine legal protection against theft of personal data and personal identity in Indonesia and to examine the law enforcement mechanisms and obstacles faced in the process.The research method used is normative juridical, with a regulatory, conceptual, and comparative approach. Data sources come from literature studies of regulations, legal literature, and relevant court decisions. The results of the study show that personal data protection in Indonesia is still in the developing stage, marked by the enactment of Law Number 27 of 2022 concerning Personal Data Protection. However, there are still limitations to norms in terms of implementation, criminal sanctions, and strong supervisory institutions. In addition, law enforcement against theft of personal data faces various obstacles, including limited authority of law enforcement officers, low public awareness of the importance of protecting personal data, and the complexity of evidence in cases of cross-border cybercrime. International efforts, such as cross-secret cooperation and extradition of perpetrators, are also still not optimal due to differences in legal systems between countries. This study recommends strengthening technical regulations for implementing the PDP Law, increasing the capacity of independent supervisory institutions, educating the public about data security, and increasing international cooperation in combating cybercrime. Effective national legal protection of personal data is an important foundation in maintaining citizens' privacy rights and building trust in the digital ecosystem.Purposes of the Research: Analyze and explain law enforcement against the crime of personal data theft on social media (Facebook).Methods of the Research: The research method used is normative juridical, with a statutory and conceptual approach. Sources of legal materials used are primary, secondary and tertiary legal materials. The technique of collecting legal materials carried out in this research is through library research, namely by searching legal materials by reading, viewing, listening and now many are done by searching through the internet then the data will be analyzed using quantitative data analysis techniques, in an approach Quantitative related to the relationship of variables analyzed using an objective theory, then described to solve the main problem in this study.Results / Findings / Novelty of the Research: Law enforcement against personal data theft in Indonesia has a strong legal basis through the Personal Data Protection Law, the Electronic Information and Transactions (ITE) Law, and other relevant regulations. However, its implementation still faces various obstacles, such as technological limitations, inadequate investigative capabilities, and difficulties in tracking and gathering evidence in the cyber realm. The cross-border nature of cybercrime also presents jurisdictional challenges, necessitating strong international cooperation mechanisms for effective law enforcement